2015
DOI: 10.1111/bju.12951
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral intraprostatic injection of botulinum neurotoxin type A for the treatment of chronic prostatitis/chronic pelvic pain syndrome: results of a prospective pilot double‐blind and randomized placebo‐controlled study

Abstract: Objective To evaluate the effect of botulinum neurotoxin type‐A (BoNT‐A) on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) refractory to medical therapy. Materials and Methods Between November 2011 and January 2013, 60 men aged ≥18 years with CP/CPPS, and with National Institutes of Health Chronic Prostatitis Symptom Index (NIH‐CPSI) scores ≥10 and pain subscale scores ≥8, who were refractory to 4–6 weeks' medical therapy, underwent transurethral intraprostatic injection of BoNT‐A or normal saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The effect of onabotulinumtoxinA (onaBoNT-A) injection on CP/CPPS was evaluated in a double-blind study in 60 males. [ 17 ] Men were injected transurethrally into their lateral prostate lobes with either placebo saline or onaBoNT-A (100 or 200 units depending on prostate size). Significant improvements in symptoms scores and QOL were observed in the onaBoNT-A group compared to placebo.…”
Section: What Does This Mean For the Urologist Treating A Patient Witmentioning
confidence: 99%
“…The effect of onabotulinumtoxinA (onaBoNT-A) injection on CP/CPPS was evaluated in a double-blind study in 60 males. [ 17 ] Men were injected transurethrally into their lateral prostate lobes with either placebo saline or onaBoNT-A (100 or 200 units depending on prostate size). Significant improvements in symptoms scores and QOL were observed in the onaBoNT-A group compared to placebo.…”
Section: What Does This Mean For the Urologist Treating A Patient Witmentioning
confidence: 99%
“…148 Findings of a prospective, randomized, doubleblind, placebo controlled trial in 60 patients with CPPS also revealed that transurethral intraprostatic BoNTA injections were effective in reducing symptom scores and pain scores, with a therapeutic efficacy significantly superior to placebo (P <0.05). 149 These pilot clinical trials do shed new light on this debilitating prostatic disease, although assessment of outcomes in these studies [147][148][149] was mainly based on patients subjective reports.…”
Section: Chronic Prostatitismentioning
confidence: 99%
“…Recently, a prospective, double-blind and randomized placebo- controlled study enrolled 60 male patients with refractory CP/CPPS to receive transurethral intraprostatic injection of 100 U of onabotulinumtoxinA or normal saline [ 87 ]. The Chronic Prostatitis Symptom Index, pain VAS, and urinary frequency significantly improved in the onabotulinumtoxinA group while none of the values improved significantly in the placebo group.…”
Section: Clinical Application Of Bont-a In Cp/cppsmentioning
confidence: 99%
“…Urinary tract infection developed in four patients (5%). In a study of 30 men with CP/CPPS, who received intraprostatic injection of onabotulinumtoxinA, only two patients complained of mild hematuria lasting less than 6 hours [ 87 ]. In terms of onabotulinumtoxinA injection in CPP due to pelvic floor muscle spasm, two women reported increased flatus, but no fecal or urinary incontinence [ 94 ].…”
Section: Adverse Events Of Bont-a Injection In Cppmentioning
confidence: 99%